Anodic dearomatization of 2-alkynylanilines for the synthesis of multi-functionalized indoles. Issue 48 (25th May 2022) - Chen, Zhuowen; He, Qiuqin; Guo, Hao; Fan, Renhua
Abstract : An anodic oxidative dearomatization of 2-alkynylaniline and its application for the synthesis of benzenoid ring multi-functionalized indoles is reported. Abstract : An anodic oxidative dearomatization reaction of 2-alkynylanilines was developed. The formed dearomatized compounds were used as versatile precursors in the synthesis of a variety of benzenoid ring multi-functionalized indoles through simple conversions.